2016
DOI: 10.1038/onc.2016.195
|View full text |Cite
|
Sign up to set email alerts
|

The ERK–ZEB1 pathway mediates epithelial–mesenchymal transition in pemetrexed resistant lung cancer cells with suppression by vinca alkaloids

Abstract: High thymidylate synthase (TS) level in cancer tissue is considered to result in resistance to pemetrexed therapy for advanced stages of nonsquamous non-small cell lung cancers. To further investigate the mechanism of pemetrexed resistance and potential prognostic outcomes in lung cancer, we established pemetrexed-resistant lung adenocarcinoma cell sublines from CL1 harboring a mutated TP53 gene (R248W) and A549 harboring wild-type TP53. We found the TS expression is upregulated in both pemetrexed-resistant su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 45 publications
10
72
1
Order By: Relevance
“…Another study by Chi LY et al. also described the IC50 of pemetrexed for A549 cells (1304.7 ± 94.7 nmol/L) . The concentration range of metformin and pemetrexed used in our study, as previously indicated, is in accordance with the results of the preliminary experiment above.…”
Section: Discussionsupporting
confidence: 91%
“…Another study by Chi LY et al. also described the IC50 of pemetrexed for A549 cells (1304.7 ± 94.7 nmol/L) . The concentration range of metformin and pemetrexed used in our study, as previously indicated, is in accordance with the results of the preliminary experiment above.…”
Section: Discussionsupporting
confidence: 91%
“…Our data show that gemcitabine treatment of mesenchymal pancreatic cells exacerbates their EMT‐like phenotype and invasiveness through ERK1/2 mediated ZEB‐1 upregulation. Interestingly, pemetrexed resistance of lung cancer cells was recently shown to be associated with induction of EMT and invasion through activation of ERK1/2‐ZEB‐1 pathway . ZEB‐1 has been shown to be associated with radioresistance and chemoresistance in several cancers including PC .…”
Section: Discussionmentioning
confidence: 99%
“…4c, our results interestingly showed that the combination treatment of eribulin and OBP-801 suppressed the MAPK pathway more effectively than single agent alone in TNBC. Recently, vincristine has also been reported in lung cancer to downregulate the phosphorylated ERK protein, resulting in the suppression of the zinc finger E-box binding homeobox 1 (ZEB1), an activator of epithelial-mesenchymal transition [15]. Eribulin has been shown to reverse epithelial-mesenchymal transition both in vitro and in vivo [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Among microtubule dynamic inhibitors, vinca alkaloids are known to suppress the MAPK pathway [15], while paclitaxel enhances it in other carcinoma cells [16]. Therefore, we investigated whether eribulin enhanced or suppressed the MAPK pathway in TNBC cells.…”
Section: Combination Treatment Of Eribulin and Obp-801 Also Suppressementioning
confidence: 99%